(3GddaX GdecQe HaVd YGThQG GdeMQes - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb efShi s
(3BNQgG (B:s
(3hUd Ydi GdeYXe ai GdHQjG QShdc CMeO CfJ GdMejO UdGI HGdSdGe Ydjg JCJi OhGekG dceG aUdJ JYhO BNQ GddaX GdecQe HaVd YGThQGA GdeMQe s
(3HgG fXGe GdJYbjs
(3cJHJ HNW eged GdfbW CMjGfkG fbdkG Yf fSNI HNW GdeDda hYdi MGTjI fSNJfG gPg SeGY heYGQVI HNW GdeDda hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg hUaMI GdZdGa CjVkG HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdeLGejYs